How does land transfer impact rural household income disparity? An empirical analysis based on the micro-perspective of farmers in China - Wang, Bo; Shao, Xuyang; Yang, Xiao; Xu, Honghai (Frontiers in Sustainable Food Systems, 2023)
Based on 2018 China Family Panel Studies data, this study uses quantile regression models and a propensity score matching (PSM) method to examine land transfer and the effects of different land transfer behaviors on the income disparity of farm households. The results show that first, participation in land transfer has a general income-increasing effect on rural households' per capita income, and the effect is more significant for rural middle-and low-income groups; this helps reduce the income disparity among rural households. Second, after distinguishing between leased-in land and leased-out land as types of participation in land transfer, this study finds that the effect of land transfer is mainly attributed to the leased-out land type, while the effect of leased-in land on increasing income and reducing income disparity are not significant. Third, the effect of leasing out land to reduce income disparity may be realized by unlocking the business and investment potential of rural non-farm industries. Moreover, compared with other areas, rural areas with potential policy interference or higher non-farm industry participation rates have weaker income-increasing effects on land transfer and weaker suppressive effects on income disparity among rural households. Therefore, to alleviate the problem of widening rural income disparity, improve rural economic vitality, and consolidate the results of poverty alleviation, farmers should continue to be encouraged to participate in land transfer.